O Amapá e a Guiana francesa sob a ótica do corredor transfronteiriço - José Alberto Tostes; José Francisco de Carvalho Ferreira (Confins)
Cross-border territories are multi-faceted, diverse and complex spaces as well as contact, articulation and cooperation spaces. Treated, for a long time, as peripheral places, they take up today as strategic ones. In this context, this article aims to address the Transboundary Corridor as a reflective basis for understanding the present and future interactions between Amapá (Brazil) and French Guiana (France), two territories with over 600 km of common border. The main purpose is to define and introduce the concept of Transboundary Corridor, offering a possibility of understanding the socio-political and economic relations of these two territories. The results show that these relationships are not yet fully perceived and developed.